Wykorzystanie metod programowania neurolingwistycznego (NLP) w kształtowaniu kultury organizacyjnej biblioteki - Katarzyna Pilitowska (Biblioteka)
Neuro-linguistic programming is one of many methods used in the West to influence people’s attitudes towards work, their way of thinking and the motivation to work. Its originality stems from the fact that the method appeals in the main to non-material values such us: service orientation, social usefulness of one’s work, the sense of duty and satisfaction it gives, the resulting feeling of one’s high self-esteem. The NLP is included in the broadly-understood organizational culture applied in a given firm or an institution. The author maintains that thus understood neuro-linguistic programming can find its application in modem library practice and significantly improve modernization processes within its organizational culture.